Along the river that flowed south - Mohlomi, Teboho Samson (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
I am drawn to the longer story form, or novella, that can be read in one sitting. I relish the challenge of creating characters and seeing the plot unravelling and taking me into different directions, in a way short prose does not. In my thesis I experiment with writing the dead back to life, hopping between different timelines in such a way as to cloud the certainty of knowing who is alive and who is dead. My writing is influenced by the gender injustices we experience in our society. As much as writing fiction is not an attempt to fix the world, I find that where there is strife and conflict around me, my need to write gets ignited, especially when that conflict is about unfairness between the sexes. Juan Rulfo's Pedro Paramo is the main inspiration for this body of work, as is Lesley Nneka Arimah's short story "Second Chances" , and Karen Lord's Redemption in Indigo. In all these works, the supernatural interacts with the natural. I'm inspired by Lord's humorous style of narrating and wish I could use it even while telling stories that otherwise have heavy themes.
Keywords: South African fiction (English) 21st century; Creative writing (Higher education) -- South Africa; Books Reviews; Diaries Authorship; South African essays (English) 21st century